Rhizoma Coptidis: A Potential Cardiovascular Protective Agent - Tan, Hui-Li; Chan, Kok-Gan; Pusparajah, Priyia; Duangjai, Acharaporn; Saokaew, Surasak; Mehmood Khan, Tahir; Lee, Learn-Han; Goh, Bey-Hing (Frontiers in Pharmacology, 2016)
Cardiovascular diseases (CVDs) are among the leading causes of morbidity and mortality in both the developed and developing world. Rhizoma coptidis (RC), known as Huang Lian in China, is the dried rhizome of medicinal plants from the family Ranunculaceae, such as Coptis chinensis Franch, C. deltoidea C.Y. Cheng et Hsiao, and C. teeta Wall which has been used by Chinese medicinal physicians for more than 2000 years. In China, RC is a common component in traditional medicines used to treat CVD associated problems including obesity, diabetes mellitus, hyperlipidemia, hyperglycemia and disorders of lipid metabolism. In recent years, numerous scientific studies have sought to investigate the biological properties of RC to provide scientific evidence for its traditional medical uses. RC has been found to exert significant beneficial effects on major risk factors for CVDs including anti-atherosclerotic effect, protection from myocardial ischemia-reperfusion injury, lipid-lowering effect, anti-obesity effect and anti-hepatic steatosis effect. These properties have been attributed to the presence of bioactive compounds contained in RC such as berberine, coptisine, palmatine, epiberberine, jatrorrhizine and magnoflorine; all of which have been demonstrated to have cardioprotective effects on the various parameters contributing to the occurrence of CVD through a variety of pathways. The evidence available in the published literature indicates that RC is a herb with tremendous potential to reduce the risks of CVDs, and this review aims to summarize the cardioprotective properties of RC with reference to the published literature which overall indicates that RC is a herb with remarkable potential to reduce the risks of CVDs.